MOLECULAR IDENTIFICATION OF TRYPANOSOMES IN WILD TSETSE FLIES CAPTURED FROM KAINJI LAKE NATIONAL PARK, NIGERIA. - Jonah, Alice; Attahir, A.; Idowu, F. M.; Usman, B. M.; Tese, T. T.; Rukayya, G.; Mercy, D.; Jabiru, G.; Isadu, H. T.; Abdulraheem, S. (FUDMA JOURNAL OF SCIENCES, 2020)
In order to detect and identify trypanosomes in the wild, and to better understand tsetse-trypanosome relationships, Tsetse flies were trapped from the Kanji-Lake Nation al Park, North-central, Nigeria, using 20 biconical Tsetse traps obtained from Nigerian Institute for Trypanosomiasis, Kaduna. The traps were deployed, covering a 10km distance on the banks of the Oli River at the park. Flies were harvested daily, sorted and preserved in absolute alcohol. A total of 234 flies were trapped in three days comprising159 females and 75 males. The apparent fly density was determined, (Fly/Trap/Day, FTD). DNA extraction was performed on 72 randomly selected flies. Extracted DNA was then subjected to PCR using ITS1 of the ribosomal DNA. Results identified all flies as Glossina tachnoides sp with an apparent fly density (FTD), of 3.93. PCR amplification indicated that 56 (78%) of the flies were infected with Trypanosoma vivax and Trypanosoma congolense (either as single or mixed infections). This infection rate of 78% is considered high and suggests a high level of flies’ vectorial capacity. Tsetse fly being a major transmitter of Animal and human Trypanosomiasis, its high vectorial capacity is a key indicator of the prevalence of the disease. The findings of this study therefore present issues of major health concerns because of the potential risk of Trypanosomiasis infection to tourists, livestock and other animals in the park and its buffer zones. A timely intervention to suppress fly population in the park is suggested.